PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN PENDIDIKAN MULTIKULTURAL DI SMK GLOBAL JATITUJUH, MAJALENGKA. - Yanti Nur'aeni; Nuruddin Araniri; Syafa'atun Nahriyah (Al-Mau'izhoh : Jurnal Pendidikan Agama Islam, 2022)
Global Jati Tujuh Vocational School is one of the schools which is a Technology, Engineering, Importation and Communication Vocational High School, researchers took a case study at the Vocational School because Global Jati Tujuh Vocational High School is one of the leading Vocational High Schools. Based on preliminary research, the students there still lacked understanding regarding this multicultural education which prompted researchers to raise the formulation of research problems. The formulation of the problem in this research is What is the Role of Islamic Religious Education Teachers in Implementing Multicultural Education in Global Jati Tujuh and What are the Supporting and Inhibiting Factors for the Role of Islamic Religious Education Teachers in Implementing Multicultural Education in Global Jati Tujuh.This study uses a descriptive qualitative approach. Data collection techniques used in this study are observation, interviews and documentation. Meanwhile, the data validity test in this study used source triangulation, method triangulation and time triangulation. Data analysis in this study used data reduction, data display, and conclusion verification. With research subjects PAI teachers and Global Students Jatiseven. The results of this study indicate that the role of Islamic Religious Education Teachers in Implementing Multicultural Education in Global Jati Tujuh has played a role in implementing multicultural education, namely by building a diversity paradigm, the learning process, providing examples outside of class hours, respecting language diversity, building social care attitudes, building anti-social attitudes. discrimination against differences.